RETRACTED: Overexpressed Tumor Suppressor Exosomal miR-15a-5p in Cancer Cells Inhibits PD1 Expression in CD8+T Cells and Suppresses the Hepatocellular Carcinoma Progression - Zhang, Hong-Yu; Liang, Hong-Xia; Wu, Shu-Huan; Jiang, He-Qing; Wang, Qin; Yu, Zu-Jiang (Frontiers in Oncology, 2021)
Background Hepatocellular carcinoma (HCC) is the most common primary liver tumor, and the main reason is the unclear pathogenesis of HCC, which leads to a high fatality rate of HCC. Therefore, it is of great clinical significance to explore the molecular mechanism of HCC and find a targeted therapeutic approach from the molecular level. Materials and Methods MicroRNA-15a-5p (miR-15a-5p) expression level was measured by bioinformatics and qRT-PCR. Luciferase assay and RIP assays were used to verify the relationship between programmed cell death protein 1 (PD1) PD 1 with miR-15a-5p. Exosomes were identified using TEM, Zetasizer Nano ZS, and western blot. Edu, Transwell, and scratch assay were performed to explore the role of miR-15a-5p or exo-miR-15a-5p on HepG2 cells progression. Results MicroRNA-15a-5p (miR-15a-5p) was decreased in HCC tissues and cell lines, which indicated a poor prognosis. Overexpression of miR-15a-5p inhibited viability, proliferation, migration and invasion of HepG2 cells. Then, we isolated exosomes from cancer cells, and found that miR-15a-5p was packaged into exosomes from cancer cells. Furthermore, exo-miR-15a-5p was secreted into CD8+ T cells, then directly inhibited PD1 expression via targeted binding. Then, we co-cultured CD8+ T cells transfected with PD1 with HepG2 transfected with miR-15a-5p, PD1 remitted the inhibitory role of miR-15a-5p on HCC progression. Conclusion Together, present study revealed exo-miR-15a-5p from cancer cells inhibited PD1 expression in CD8+ T cells, which suppressed the development of HCC.